Pengembangan E-Modul Interaktif Berbasis Qr Code Pada Pembelajaran IPS Materi Keberagaman Budaya Indonesia Kelas IV Sekolah Dasar - Kasmawati, Kasmawati; Ismi, Yaqfiru Ala; L. Parisu, Chairan Zibar; Saputra, Erwin Eka; Ekadayanti, Waode (Mataram University, 2025)
This research aims to develop a QR code-based interactive e-module for social studies learning about Indonesian cultural diversity. This type of research is Research and Development (research and development). The development model used is the ADDIE (Analysis, Design, Development, Implementation and Evaluation) development model developed by Robert Maribe Brach. This development research produces products that meet validation by material experts reaching 100% in the very valid category, media experts reaching 100% in the very valid category, language experts reaching 89% in the very valid category. Furthermore, for the practicality of interactive E-module teaching materials, the student questionnaire results were 99% and the teacher questionnaire results were 100%. So it can be concluded that the development of a QR code-based interactive E-module in social studies learning material on Indonesian cultural diversity is very valid and practical for use as teaching material on Indonesian cultural diversity material in class IV A at SD Negeri 1 Ranomeeto.